Investigations of the main oral alterations in Apae students — lem with down syndrome: Influences and quality of life - Siqueira, Lahis Lara Miranda; Oliveira, Ana Clara Batista; Vieira , Bruna Evilin Silva; Filha , Liliane Carmo da Silva; Alves, Lorena Lais da Silva; Lemos , Maria Inês Ferreira; Inácio , Keila de Oliveira (Seven Editora, 2023)
Down syndrome is a congenital anomaly caused by the presence of an extra chromosome in pair 21. Patients with this syndrome have some oral alterations, namely: low prevalence of caries, periodontal diseases, fissure tongue, hypotonic or protruding tongue, malocclusion, TMJ alteration, dental agenesis, among other oral alterations. It is an epidemiological study carried out on APAE students of the descriptive type of case series, applied with the objective of explaining a quantitative approach, using oral evaluation, questionnaires for data collection and analysis, so that it can provide an adequate diagnosis and treatment, aiming at a better quality of life for them. It is essential to carry out follow-up through a multidisciplinary team from childhood, which will provide continuous treatment of these patients, obtaining confidence and improving quality of life, enabling stimuli to improve cognitive development, acting in health promotion and disease prevention. DOI:https://doi.org/10.56238/sevened2023.006-059